Narrow-leafed lupin (Lupinus angustifolius L.) seed β-conglutins reverse the induced insulin resistance in pancreatic cells. Issue 10 (26th September 2018) - Lima-Cabello, Elena; Morales-Santana, Sonia; León, Josefa; Alché, Victor; Clemente, Alfonso; Alché, Juan D.; Jimenez-Lopez, Jose C.
Abstract : Narrow-leafed lupin β-conglutin proteins may help to prevent and treat insulin resistance through pleiotropic effects. Abstract : Insulin resistance (IR) is the main contributor to the development of type 2 diabetes. In this study, we have purified recombinant β-conglutin proteins (rβ1 to rβ4, and rβ6) from narrow-leafed lupin (NLL) by using affinity chromatography. The objective of this study was to evaluate the capacity of these β-conglutins to improve the IR state using ex vivo and in vitro systems. rβ1, rβ3, and rβ6 produced lower levels of pro-inflammatory mediator nitric oxide (about -7-fold in all cases), up-regulated mRNA expression levels of IRS-1 (+201, +173, +192%) and Glut-4 (+286, +121, +147%), increased levels of p85-PI3K (+188, +187, +137-fold) and Glut-4 (+503, +548, +515-fold) proteins, higher phosphorylation levels of the insulin signalling pathway activator p-IRS-1 and downstream mediators such as p-Akt, p-Cbl, and p-caveolin, and improved glucose uptake in insulin resistant (IR-C) culture cells. β-conglutin proteins were able to suppress the oxidative stress produced by insulin-induced resistance on PANC-1 control (C) cells by strongly reducing the protein oxidative carbonylation induced by ROS and balancing the metabolic homeostasis in IR-C cells through regulation of mRNA expression. At the same time, β-conglutins are able to reduce the levels of the pro-inflammatory mediator nitric oxide and promote the anti-oxidative capacity of cells by increasing the levels of reduced glutathione. These results suggest NLL β-conglutins might play a fundamental role as functional food components, since β-conglutins' nutraceutical properties could enhance the effectiveness of dietary improvement of type 2 diabetes complications.